Efisiensi teknis usahatani kentang pada luas lahan yang berbeda di kabupaten Pasuruan - Utami, Desy Cahyaning; Mamilianti, Wenny (Fakultas Pertanian Universitas Yudharta Pasuruan, 2021)
Potatoes are upland vegetable crops, which is the superior plant of Tosari District, Pasuruan Regency. Tosari potatoes are the largest contributor to production in East Java. The farmer profession is the main profession in this area, inherited from the family. The land area owned is inherited from the family. The agricultural land area varies, but still found farmers with a land area of more than one hectare. In this study, respondents were divided into two groups, namely farmers with a land area of ≥ 1 hectare called cluster I and respondent farmers with a land area of ≤ 0.5 hectares called cluster II. The purpose of this study was to analyze the effect of production inputs on potato production, to analyze the level of technical efficiency of potato farmers with different land areas, to analyze the factors affecting the level of technical efficiency. The study was conducted by interviewing 49 respondent farmers in Cluster I and 70 respondent farmers in Cluster II. This study uses the Cobb Douglas production function, the analytical methods used are the Stochastic Analysis Frontier (SFA) and the Tobit regression analysis. The results showed that the production inputs that had a significant effect on production in cluster I were seeds, fertilizers, and manure, while in cluster II were fertilizers and pesticides. The level of technical efficiency of farmers who have a land area of ≥ 1 hectare is greater than farmers with a land area of ≤0.5 hectares. The land area has a significant effect on the level of technical efficiency.